Prolit computer system for modelling the flow of cooling melts into the casting bed - A. N. Chichko; S. G. Likhouzov; V. F. Sobolev (Литьë и металлургия)
The article describes the structure of the programme project for three-dimensions modelling of the cooling melt flow. It presents the data on filling and crystallization of the Radiator casting manufactured at MZOO. These data was calculated with the help of a developed computer system.